Sistem Pendukung Keputusan Persetujuan Kredit Mobil Dengan Metode Fuzzy Logic - Seny Luhriyani (STMIK KHARISMA Makassar, 2016)
The research aimed to develop a decision supporting system for a company as the helping aid of a decision-making to give the car credit agreement to the customers in order that they could obtain the result of their credit applications quickly. The system was designed using the decision supporting method of Fuzzy Logic with the criteria of identity, guarantee, income and occupation. System building software used the program of Borland Delphi 10 with the database MySQL. The system examination was conducted by the black box method. The results of the research reveals that the decision supporting system designed can produce information quickly so that it can be used as the decision-making in the car credit agreement.